Decision Support System for Share Investment Using The Capital Assetpricing Method (CAPM) - Andriani Putri Wihartati; Tino Feri Efendi (International Journal of Computer and Information System (IJCIS), 2021)
Investment is the placement of a number of funds at this time with the hope of obtaining benefits in the future. Stocks are one of the most popular investments. The current millennial generation is interested in investing in stocks because the capital required is not too large. However, in choosing a good stock for investment, the ability to read financial ratios is required. Errors in reading financial ratios will cause stock investment not to go as expected. To help with this, a system capable of supporting decisions is needed. There are several methods that can be used to produce a decision support system. In this study, the authors use the Capital Asset Pricing Model (CAPM) method in designing a decision support system in stock investment selection.The method in this research is through observation, interview, and literature study. The system design is made using Contex Diagram, HIPO, DAD, and database design. The system is made in a program with the PHP programming language. The process of determining the selection of stock investments using the Capital Asset Pricing Model (CAPM) method can simplify the determination process. Then with the method. can make it easier to determine the selection of stock investment.The final result in the stock investment selection process is a report that states investment (Ri> E) or not investment (Ri <E).